2015
DOI: 10.1111/ddg.12737
|View full text |Cite
|
Sign up to set email alerts
|

Green tea in dermatology – myths and facts

Abstract: Summary Green tea consumption has a long tradition in Asian countries – especially China. The epidemiologically and experimentally observed anticarcinogenic and antiinflammatory effects of green tea have led to the implementation of green tea extracts in multiple therapeutic applications – both in dermatological and cosmeceutical preparations. The most abundant evidence exists for the anticarcinogenic and chemopreventive effect of green tea or its major constituent epigallocatechin‐3‐gallate. Almost equally ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
2
23
0
4
Order By: Relevance
“…(25) Polyphenols in green tea may inhibit the activity of collagenase and increase the biosynthesis of collagen in fibroblasts to further protect the skin from free radicals. (9,26,27) Moisturizers protect the skin through occluding the TEWL process by creating a protective layer above the stratum corneum. Another mechanism is by increasing water absorption into the stratum corneum (humectant), and filling the gap between desquamating keratinocytes to create a softer skin (emollient).…”
Section: Discussionmentioning
confidence: 99%
“…(25) Polyphenols in green tea may inhibit the activity of collagenase and increase the biosynthesis of collagen in fibroblasts to further protect the skin from free radicals. (9,26,27) Moisturizers protect the skin through occluding the TEWL process by creating a protective layer above the stratum corneum. Another mechanism is by increasing water absorption into the stratum corneum (humectant), and filling the gap between desquamating keratinocytes to create a softer skin (emollient).…”
Section: Discussionmentioning
confidence: 99%
“…Sinecatechins (green tea extract) ointment has been found effective in the therapy of condylomata accuminata, being the first botanical drug approved for prescription by the US Food and Drug Administration [70]. Similarly, the topical administration of green tea extract has yielded promising results in the treatment of rosacea, acne, and atopic dermatitis [70].…”
Section: Discussionmentioning
confidence: 99%
“…Sinecatechins (green tea extract) ointment has been found effective in the therapy of condylomata accuminata, being the first botanical drug approved for prescription by the US Food and Drug Administration [70]. Similarly, the topical administration of green tea extract has yielded promising results in the treatment of rosacea, acne, and atopic dermatitis [70]. However, as evidence arises that orally administered green tea may exert biological effects in the skin, further research is needed to evaluate the effectiveness of green tea supplementation in the treatment and prevention of dermatological conditions, especially those associated with oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these diseases, it can be used to prevent or treat AGA by selectively inhibiting 5α-reductase activity. Catechins, a group of very active flavonoids, are a major component of green tea representing 60-80% of all polyphenols [44,45]. There are four major catechins in green tea: epigallocatechin-3-gallate (ECGC), epigallocatechin (EGC), epicatechin gallate, and epicatechin [46,47].…”
Section: Green Teamentioning
confidence: 99%
“…There are four major catechins in green tea: epigallocatechin-3-gallate (ECGC), epigallocatechin (EGC), epicatechin gallate, and epicatechin [46,47]. ECGC is the most highly bioactive catechin among these constituents [45]. In a study, EGCG was found to cause significant human hair follicle elongation ex vivo.…”
Section: Green Teamentioning
confidence: 99%